Analisis Perbedaan Sistem Perbankan Konvensional dan Perbankan Syariah Dalam Sistem Perbankan Indonesia - Hidayah, Nur; B, Baidhowi; Novita, Yustina Dhian (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This article analyzes the differences between conventional banking and Islamic banking systems in Indonesia, focusing on their operational principles and products. Indonesia, as a country with a large population and a Muslim majority, has two banking systems, namely conventional banking and Islamic banking. This article aims to provide a better understanding of these two banking systems and their implications for the development of an inclusive and sustainable financial system in Indonesia.